2005
DOI: 10.1002/ijc.21600
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and cancer risk in a population‐based case–controlstudy among men from Montreal, Canada

Abstract: Diabetics may have a higher risk of cancer, notably liver and pancreatic cancers. Evidence about other cancer types remains sparse. The authors examined potential associations between diabetes and several types of cancer in a large multicancer case-control project carried out in Montreal, Canada, in the 1980s. This report, based on 3,107 male cancer cases and 509 population controls, uses information on diabetes and several covariates collected by interview. Adjusted odds ratios (ORs) and 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
99
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 40 publications
6
99
0
5
Order By: Relevance
“…To date, many large sample epidemiological studies have investigated the important role of DM in bladder cancer development. The results were inconsistent or even contradictory, some of studies did not support an association of DM with overall bladder cancer incidence (Rousseau et al, 2006;Larssona et al, 2008;Zhang et al, 2012). So after removing the three unqualified literature (Kessler, 1970;Kantor et al, 1984;Verlato et al, 2003), adding the new studies which were not included in above meta-analysis, we performed a meta-analysis of 23 published studies covering 643,683 cases and 4,819,656 controls to get a more precise evaluation of the association between DM and the risk of bladder cancer.…”
Section: Diabetes Mellitus Increases the Risk Of Bladder Cancer: An Umentioning
confidence: 98%
See 3 more Smart Citations
“…To date, many large sample epidemiological studies have investigated the important role of DM in bladder cancer development. The results were inconsistent or even contradictory, some of studies did not support an association of DM with overall bladder cancer incidence (Rousseau et al, 2006;Larssona et al, 2008;Zhang et al, 2012). So after removing the three unqualified literature (Kessler, 1970;Kantor et al, 1984;Verlato et al, 2003), adding the new studies which were not included in above meta-analysis, we performed a meta-analysis of 23 published studies covering 643,683 cases and 4,819,656 controls to get a more precise evaluation of the association between DM and the risk of bladder cancer.…”
Section: Diabetes Mellitus Increases the Risk Of Bladder Cancer: An Umentioning
confidence: 98%
“…However there were still some limitations in this published meta-analysis: (1) The studies and samples were insufficient for which did not contained many new studies with a large number of samples which reported in recent years (Manami et al, 2006;Rousseau, 2006;Susanna et al, 2008;Li et al, 2011;MacKenzie et al, 2011;Tseng, 2011;Attner et al, 2012;Zhang et al, 2012;Newton et al, 2013;Prizment et al, 2013). So the population included in it was too small to reveal the actual relationship between DM and the bladder cancer risk.…”
Section: Diabetes Mellitus Increases the Risk Of Bladder Cancer: An Umentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] In the Västerbotten Intervention Project of northern Sweden, total cancer risk in women increased with rising plasma levels of fasting and postload glucose, up to a relative risk for the top versus bottom quartile of 1.26 and 1.31, respectively. 1 Risk of cancer of the pancreas, endometrium, urinary tract and of malignant melanoma was statistically significantly associated with high fasting glucose, which was totally independent on age, smoking and body mass index.…”
mentioning
confidence: 99%